Development of Legal Regulation of Electronic Vote in Russia - Yaroslav Valeryevich Antonov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article discusses the features of the evolution of legal regulation of e-voting in Russia. The article deals with the emergence of e-voting, the first experiments on its implementation in the Russian electoral practices. The author analyzed of legal acts in chronological order as they are adopted, given the legal assessment of the changing approaches of the Central Election Commission of the Russian Federation to the legal regulation of electronic voting depending on the success of experiments on its implementation in the electoral practices and the electoral process. Analyzed the concept of e-voting, including the historical perspective, especially refined understanding of e-voting in Russia in comparison with the international approach to the definition of the concept. Particular emphasis is placed on the fact that in Russia under the electronic voting refers to electronic voting at polling stations, and it is using electronic voting systems (KEG). Not an electronic voting ballot using complex processing of ballots (KOIB). Author was comprehensive studying of the state automated system “Elections” (GAS “Elections”), including the historical perspective, the basic part of the SAS “Elections”, not only in terms of their functional and technical purposes, but also in relation to the e-voting system. In the article was described the experiments on the introduction of remote electronic voting using different devices (CDs, electronic keys) within the practice of electronic surveys. Among the most interesting results of experiments on the introduction of remote e-voting has been an increase voter confidence in relation to electronic voting as to enhance their legal and information culture in this area. Particular attention is paid to the development prospects of e-voting in Russia in terms of the possibility of introducing e-voting in referendums, as well as the introduction of Internet voting. In conclusion was considered main mechanisms, trends and prospects for improving the regulatory framework of electronic voting, including in connection with technological innovations in the electoral process. Attention is paid to the prospects of upgrading the existing technological infrastructure for new long-term objectives.